A novel current‐source management integrated circuit applied to high‐voltage integrated gate commutated thyristor gate driver - Shiping Chen; Zhanqing Yu; Jiaxu Shi; Zhengyu Chen; Lu Qu; Jinpeng Wu; Rong Zeng (High Voltage, 2025)
Abstract This paper presents a fully customised integrated gate commutated thyristor (IGCT) gate driver monolithic integrated circuit (GDMIC), aiming to address the many shortcomings of traditional IGCT gate driver units composed of discrete components, such as the excessive number of components, low reliability, and complex development processes. The current‐source driving characteristics of IGCTs pose significant technical challenges for developing fully customised integrated circuits (IC). The customised requirements of IGCT gate driver chips under various operating conditions are explored regarding functional module division, power sequencing, and chip parameter specifications. However, existing high‐side (HS) driver methods exhibit limitations in functional monolithic integration and bipolar complementary metal‐oxide‐semiconductor compatibility. To address these challenges, a novel HS driving topology based on floating linear regulators is proposed. It can achieve synchronised control of multi‐channel floating power transistors while supporting 100% duty cycle continuous conduction. The proposed GDMIC reduces the three independent HS power supplies to a single multiplexed topology, significantly decreasing circuit complexity. Experimental results validate the feasibility and performance of a 4‐inch gate driver prototype based on IGCT current‐source management IC, demonstrating significant advantages in reducing the number of components, enhancing device reliability, and simplifying development. The proposed GDMIC offers an innovative development path for future high‐power IGCT drivers.